COMMENTS TO THE PAPER S. NODARI ET AL. «EFFECTS OF N-3 POLYUNSATURATED FATTY ACIDS ON LEFT VENTRICULAR FUNCTION AND FUNCTIONAL CAPACITY IN PATIENTS WITH DILATED CARDIOMYOPATHY» - S. N. Tereshchenko (Столичная издательская компания, 2016)
.